(untitled) (Research, Society and Development, 2020)
Dengue is an emerging infectious disease, transmitted by mosquitoes of the genus Aedes, particularly Ae. aegypti and Ae. albopictus. The tropical climate, vast territory and large flow of people in Brazil are factors that provide expressive epidemics of dengue vírus (DENV). In this context, the research aimed to analyze the space-temporal distribution of the trend of the numbers of dengue cases in Pernambuco state. The database was composed by weeklys epidemiological records about the dengue cases from 2000 to 2018, made available through the Information and Communication Secretariat (SIC). Spatial distribution of dengue clinical pictures demonstrated a high concentration on the coast of the state, with a higher frequency of cases in the Metropolitan Region of Recife (100%), followed by Mata Pernambucana (71,42%), Agreste Pernambucano (60,56%), San Francisco Pernambucano (60,0%) e Sertao Pernambucano (36,58%). Spatialization of the permitted trend outlines the epidemiological scenario of the numbers of dengue cases, consisting a tool capable of guiding strategic planning for epidemic control in Pernambuco in order to reduce the growth rampant of the disease.